Procédé de préparation de polymères á base de Silicium = Process for the preparation of silicon-based polymers - Corriu, Robert; Huille, Sylvain; Enders, Markus; Moreau, Joel (Espacenet, 1995)
Process for the preparation of silicon-based polymers, characterised in that at least one oligomer of the following formula (1): in which formula (1) n is an integer between 4 and 10, R<1> denotes a hydrocarbon radical and R denotes a radical chosen from hydrocarbon organosiloxane and organosilazane groups, is brought into contact with a catalytic quantity of an organometallic derivative of transition metals.